IMPACT OF AGRICULTURAL LAND CONVERSION FOR SOCIO-ECONOMIC COMMUNITY IN AIR PACAH VILLAGE KOTO TANGAH SUBDISTRICT IN PADANG CITY - Febriani, Trina - (Pendidikan Geografi, 2014)
The aims of the research are to get the data , process, analyze and discuss the impact of the conversion of agricultural land for socio-economic communities in the Air Pacah Village Koto Tangah subdistrict in Padang viewed from education level , live lihood changing, the level of ownership assets , and infrastructure facilities .This research is descriptive qualitative. population of the research is affected communities from land conversion in the Air Pacah Village. The sample of respondents was taken by a proportional random sampling of 20 % of people were affected by a conversion of agricultural land become 112 families for respondentThe research of the study explain that : (1) The conversion of farmland impact on positively public education in the Air Pacah Village, (2) the conversion of farmland impact on positively peoples livelihood in theAir Pacah Village, (3) conversion of agricultural land impact for the ownership of assets by people in the Air Pacah Village, (4) conversion of agricultural land impact of existing infrastructure facilities in the Air Pacah Village . Conversion of agricultural land in the Air Pacah Village is essential for the socio-economic circumstances of local communities , there are positive and negative impactsif we look at bath sides that can be understood are very important role in the welfare of the people in the Air Pacah Village Koto Tangah subdistrict in Padang city.